W. Ross Silcock letter to Nicholas S. Halmi regarding winter bird sightings, February 28, 1979 - Silcock, W. Rosset al (1979)
Letter from W. Ross Silcock to Nicholas S. Halmi regarding winter bird sightings. February 28, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed